Research Trends and Challenges in Smart Grids - Vaccaro, Alfredo; Faheem Zobaa, Ahmed; Karthikeyan Shanmugam, Prabhakar; Sathish Kumar, Kannaiah (IntechOpen, 2020)
This book introduces the most promising enabling technologies and methodologies for smart grids. It not only focuses on technological breakthroughs and roadmaps in implementing these technologies, but also presents the much-needed sharing of best practices, demonstrating the potential role of smart grid functions in improving the technical, economic, and environmental performance of modern power distribution systems. This can be achieved by allowing for massive pervasion of dispersed generating units, increasing the hosting capacity of renewable power generators, reducing active power losses and atmospheric emissions, and improving system flexibility.